2001
DOI: 10.1016/s0925-4439(00)00092-2
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E acts to increase nitric oxide production in macrophages by stimulating arginine transport

Abstract: Previous studies have shown that apolipoprotein E (apoE) plays a role in immune function by modulating tissue redox balance. Using a mouse macrophage cell line (RAW 264.7), we have examined the mechanism by which apoE regulates nitric oxide (NO) production in macrophages. ApoE potentiates NO production in immune activated RAW cells in combination with lipopolysaccharide or polyinosinic:polycytidylic acid (PIC), agents known to induce expression of inducible nitric oxide synthase mRNA and protein. The effect is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…An additional key amino acid for renewal of the intestinal epithelium is arginine, which is often deficient in malnourished patients. Indeed, it is an arginine-selective cationic amino acid transporter that is upregulated by the ApoE4 allele associated with protection from the cognitive effects of diarrhea and malnutrition (16,17), and this observation could explain, at least in part, the protective effect of the allele (57). Arginine might also provide a novel epithelial repairing therapy, and it was well tolerated in premature neonatal human infants, in whom it reduced the incidence of necrotizing enterocolitis (165).…”
Section: Scientific Challenges That Remainmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional key amino acid for renewal of the intestinal epithelium is arginine, which is often deficient in malnourished patients. Indeed, it is an arginine-selective cationic amino acid transporter that is upregulated by the ApoE4 allele associated with protection from the cognitive effects of diarrhea and malnutrition (16,17), and this observation could explain, at least in part, the protective effect of the allele (57). Arginine might also provide a novel epithelial repairing therapy, and it was well tolerated in premature neonatal human infants, in whom it reduced the incidence of necrotizing enterocolitis (165).…”
Section: Scientific Challenges That Remainmentioning
confidence: 99%
“…For example, the APOE allele APOE4, which is associated with increased risk for cardiovascular and Alzheimer disease, was discovered to protect against the cognitive ravages of diarrhea (16). Because ApoE4 has been shown to drive an arginineselective transporter (17), these observations uncover a potential novel approach to repairing the damaged intestinal epithelium in individuals infected with enteric pathogens using arginine or its precursors, such as glutamine. It is therefore imperative that we understand the epidemiology, etiologies, and pathophysiology of enteric infections, as well as host-pathogen interactions, if we are to elucidate innovative interventions to control the still-devastating consequences of repeated malnourishing and disabling enteric infections in the most formative early years of childhood.…”
Section: Introductionmentioning
confidence: 99%
“…19 It has been demonstrated that apoE can directly increase intracellular NO via activation of NO synthase in both platelets and endothelial cells. 13,20,21 Conversely, epidemiological and experimental data have demonstrated an opposing role of apoE4 on various inflammatory processes. For example, studies have demonstrated that the 4 isoform is proinflammatory, 22 possibly through direct oxidant properties 19,23 or through deficits in NO signaling.…”
mentioning
confidence: 99%
“…Arginine uptake was measured essentially as described by Colton et al (2001). CAD cells were plated into 24-well dishes and preequilibrated in serum-free media containing low arginine (10 M).…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular arginine pools are primarily supplied by arginine transporters that move arginine across the plasma membrane to the interior of the cell. Although arginine transport can regulate NO production in macrophages (Kakuda et al, 1999;Colton et al, 2001), some neuronal populations maintain intracellular arginine pools by recycling citrulline through the citrulline-arginine-NO cycle, thus bypassing arginine uptake (Braissant et al, 1999;Heneka et al, 2001). To determine whether CAD cells synthesize arginine via this mechanism, we examined the expression of argininosuccinate lyase (AL) and argininosuccinate synthase (AS), the two enzymes necessary for the citrulline-arginine-NO cycle.…”
Section: Arginine Transport Is Increased In Pathological-length Polyqmentioning
confidence: 99%